The gut microbiome dysbiosis and regulation by fecal microbiota transplantation: umbrella review - Zhang, Xianzhuo; Luo, Xufei; Tian, Liang; Yue, Ping; Li, Mengyao; Liu, Kefeng; Zhu, Daoming; Huang, Chongfei; Shi, Qianling; Yang, Liping; Xia, Zhili; Zhao, Jinyu; et al. (Frontiers in Microbiology, 2023)
Background: Gut microbiome dysbiosis has been implicated in various gastrointestinal and extra-gastrointestinal diseases, but evidence on the efficacy and safety of fecal microbiota transplantation (FMT) for therapeutic indications remains unclear.The gutMDisorder database was used to summarize the associations between gut microbiome dysbiosis and diseases. We performed an umbrella review of published meta-analyses to determine the evidence synthesis on the efficacy and safety of FMT in treating various diseases.Our study was registered in PROSPERO (CRD42022301226).Results: Gut microbiome dysbiosis was associated with 117 gastrointestinal and extra-gastrointestinal. Colorectal cancer was associated with 92 dysbiosis. Dysbiosis involving Firmicutes (phylum) was associated with 34 diseases. We identified 62 published meta-analyses of FMT. FMT was found to be effective for 13 diseases, with a 95.56% cure rate (95% CI: 93.88-97.05%) for recurrent Clostridioides difficile infection (rCDI). Evidence was high quality for rCDI and moderate to high quality for ulcerative colitis and Crohn's disease but low to very low quality for other diseases.Conclusions: Gut microbiome dysbiosis may be implicated in numerous diseases. Substantial evidence suggests FMT improves clinical outcomes for certain indications, but evidence quality varies greatly depending on the specific indication, route of administration, frequency of instillation, fecal preparation, and donor type. This variability should inform clinical, policy, and implementation decisions regarding FMT.